Establishing a COVID-19 Vaccine Clinic at a Student-Run Free Clinic - Brandon Moritz; Tram Le; Dale Bratzler (Journal of Student-Run Clinics, 2022)
Coronavirus Disease 2019 (COVID-19) is a highly contagious infectious disease associated with significant rates of morbidity and mortality. With limited treatments for COVID-19, the most effective strategy developed to mitigate the effects of this disease is vaccination. Unity Clinic, an interdisciplinary, student-run free clinic (SRFC) at the University of Oklahoma Health Sciences Center (OUHSC), created a COVID-19 vaccine clinic that started in January 2021 to participate in the mass vaccination campaign in Oklahoma. Health profession students from seven different colleges present at OUHSC served in either non-clinical or clinical volunteer roles at the vaccine clinics. Between January 6 and July 16, 2021, Unity Clinic hosted 119 vaccine clinics, administered 39,665 vaccines, and had 16,830 student volunteer hours logged. The vaccines administered through Unity Clinic composed 1.2% of all vaccines administered in the state and 11.1% of all vaccines administered in Oklahoma County. This descriptive report demonstrates the effective use of an SRFC for large-scale COVID-19 vaccination events. Unity Clinic’s COVID-19 vaccine clinic has the potential to serve as a model for other SRFCs around the country to use for the current COVID-19 pandemic and adapt for other public health issues in the future.